Motivation in Sport: Bridging historical and contemporary theory through a qualitative Approach - Leidl, D. (International Journal of Sports Science and Coaching, 2009)
From intrinsic and extrinsic motivation to attributions and goal orientation, theory and study related to motivation in sport abound. However, theorists such as Adler, Frankl, and Maslow detail broader motivational frameworks that focus on a human impulse to derive meaning and purpose by extending beyond the self. While such theories take prominent positions within psychology, their applicability to sport has seemingly been overlooked. In an effort to explore more traditional motivational constructs in sport, a qualitative analysis of elite lacrosse coaches (n = 7) was conducted. Through semi-structured interviews, coaches shared their motivation to coach and how they motivate others. In these interviews coaches articulated a number of motivational constructs that extend beyond much of the contemporary theory. In analyzing these interviews, it is apparent that further work related to broader motivational constructs may be required to more wholly define motivation in sport.